The emergence of language differences in artificial codes - Hong, Fuhai (2019)
The paper studies how common codes of artificial language in communication are developed in the laboratory. We find that codes emerging from an environment with more variable spatial positions tend to use a limited set of symbols to represent positions, whereas codes emerging from an environment with more variable geometric shapes tend to discriminate among shapes. The paper also experimentally shows that “language” affects the way its “speakers” share the view about a novel figure.